Isotopic Evidence for Garden Hunting and Resource Depression in the Late Woodland of Northeastern North America. Issue 1 (January 2021) - Guiry, Eric; Orchard, Trevor J.; Needs-Howarth, Suzanne; Szpak, Paul
Abstract : Resource depression and garden hunting are major topics of archaeological interest, with important implications for understanding cultural and environmental change. Garden hunting is difficult to study using traditional zooarchaeological approaches, but isotopic analyses of animals may provide a marker for where and when people exploited nondomesticated animals that fed on agricultural resources. To realize the full potential of isotopic approaches for reconstructing garden hunting practices—and the impacts of agriculture on past nondomesticated animal populations more broadly—a wider range of species, encompassing many "ecological perspectives, " is needed. We use bone-collagen isotopic compositions of animals ( n = 643, 23 taxa, 39 sites) associated with the Late Woodland ( AD 900−1650) in what is now southern Ontario to test hypotheses about the extent to which animals used maize, an isotopically distinctive plant central to subsistence practices of Iroquoian-speaking peoples across the region. Results show that although some taxa—particularly those that may have been hard to control—had substantial access to maize, most did not, regardless of the animal resource requirements of local populations. Our findings suggest that this isotopic approach to detecting garden hunting will be more successful when applied to smaller-scale societies.